Aparatus Kekuasaan dalam Kebijakan UU TNI - Prastiyo Umardani (Jurnal Hukum dan Sosial Politik, 2025)
The Indonesian National Army Law (UU TNI) is a legal product that regulates the role, function and authority of the TNI in the Indonesian constitutional system. In the context of this policy, the power apparatus plays a role in the formation, implementation and supervision of regulations governing the TNI. The power apparatus includes the executive, legislative, and actors who have an interest in the state's defense and security structure. In policy formation, political actors and government institutions play a dominant role in formulating regulations that balance civilian and military interests. The implementation of the TNI Law is also greatly influenced by how power is exercised, both in the defense bureaucratic aspect and in the relationship between the military and the civilian government. The tendency for politicization of military institutions can occur if there is excessive intervention from political power in determining strategic defense policies. Apart from that, the power dynamics in the TNI Law policy are also related to how control and supervision mechanisms are implemented. Security sector reform requires a balance between civilian supremacy and military professionalism to ensure that the regulations made do not conflict with democratic principles. Therefore, understanding the power apparatus in the TNI Law policy is important in examining the extent of the role and influence of political actors on the regulations governing military institutions in Indonesia.